2009
DOI: 10.1002/pmic.200800449
|View full text |Cite
|
Sign up to set email alerts
|

Protein composition of oil bodies from mature Brassica napus seeds

Abstract: Seed oil bodies (OBs) are intracellular particles storing lipids as food or biofuel reserves in oleaginous plants. Since Brassica napus OBs could be easily contaminated with protein bodies and/or myrosin cells, they must be purified step by step using floatation technique in order to remove non-specifically trapped proteins. An exhaustive description of the protein composition of rapeseed OBs from two double-zero varieties was achieved by a combination of proteomic and genomic tools. Genomic analysis led to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
87
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 62 publications
6
87
1
Order By: Relevance
“…Lipid droplets have been observed in many mammalian cells and tissues, and it is currently thought that all ( 27 ). A 2011 study examined the accumulation of lipids and proteins during seed formation by analyzing both whole seed and purifi ed lipid droplets ( 28 ).…”
Section: Mammalian Cells and Tissuesmentioning
confidence: 99%
“…Lipid droplets have been observed in many mammalian cells and tissues, and it is currently thought that all ( 27 ). A 2011 study examined the accumulation of lipids and proteins during seed formation by analyzing both whole seed and purifi ed lipid droplets ( 28 ).…”
Section: Mammalian Cells and Tissuesmentioning
confidence: 99%
“…A 27-kDa-caleosin and a 25-kDa-caleosin have been identified in B. napus embryos (Hernandez-Pinzon et al 2001); a seed-specific caleosin has also been identified in seed of oilseed rape by Katavic et al (2006). Nine caleosins (including seven BnCLO1/2 and two BnCLO3) had been assembled from the EST-library of B. napus using A. thaliana sequences as probes, seven of which (including five BnCLO1/2 and two BnCLO3) have been confirmed by means of proteomics (Jolivet et al 2009). The newly-identified BnCLO1/2 sequences do not fit the number of caleosin genes assembled from the B. napus EST database.…”
Section: Caleosin Gene Families and Their Expansion Patterns In Brassmentioning
confidence: 99%
“…A 27-kDa-endoplasmic reticulum (ER)-localized caleosin and a 25-kDa-lipid droplet-localized caleosin have been identified from the embryos of B. napus (Hernandez-Pinzon et al 2001) and seed-specific caleosins have been identified in high and low erucic acid cultivars of B. napus (Katavic et al 2006). According to the sequences of AtCLO1-AtCLO3, nine caleosins had been identified from the ESTs library of B. napus, seven of which have been verified by means of proteomics (Jolivet et al 2009). Hu et al (2013) have identified 11 caleosins from B. rapa using bioinformatics, and performed a phylogenetic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The protein composition of seed OBs has been determined for several plant species, including Brassica napus (Katavic et al, 2006;Jolivet et al, 2009) and Arabidopsis (Jolivet et al, 2004;D'Andréa et al, 2007;Vermachova et al, 2011). In Arabidopsis, 10 proteins have been identified, and seed-specific oleosins represent up to 79% of the OB proteins (Jolivet et al, 2004;D'Andréa et al, 2007;Vermachova et al, 2011).…”
mentioning
confidence: 99%